Experimental and correlation of viscosity and refractive index of non-aqueous system of diethanolamine (DEA) and dimethylformamide (DMF) for CO2 capture - Murshid, G. (Elsevier B.V., 2018)
This paper reports the experimental refractive index and viscosity data of non-aqueous system of diethanolamine (DEA) and dimethylformamide (DMF). The refractive index and viscosity were measured for several mole fractions at atmospheric pressure and in the temperature range from 298.15 to 343.15 K with a regular interval of 5 K. The experimental refractive index data was used to derive the properties including electronic polarization, molar refraction, and specific refraction. For correlation study, the experimental refractive index was fitted into modified Graber equation and a mathematical equation called Jouyban-Acree model (JAM) and modified Vogel-Tamman-Fulcher (VTF) equation for the viscosity data. The results disclosed that JMA is more accurate for correlation of refractive index of the studied binary mixture. In order to investigate the significance of temperature and concentration on the experimental data, response surface methodology (RSM) was applied. The analysis of variance (ANOVA) showed that both temperature and concentration have a great effect on the properties. The results disclosed that as the mole fraction of DEA in the mixture increases the value of all properties increases. There was a decreasing trend in the value of all properties as the temperature increases excepting molar refraction. Â© 2017 Elsevier B.V.